2014
DOI: 10.1371/journal.pone.0087046
|View full text |Cite
|
Sign up to set email alerts
|

Are Immigrants and Nationals Born to Immigrants at Higher Risk for Delayed or No Lifetime Breast and Cervical Cancer Screening? The Results from a Population-Based Survey in Paris Metropolitan Area in 2010

Abstract: ObjectivesThis study aims to compare breast cancer screening (BCS) and cervical cancer screening (CCS) practices of French women born to French parents with those of immigrants and nationals born to immigrants, taking their socioeconomic status into account.MethodsThe study is based on data collected in 2010 in the Paris metropolitan area among a representative sample of 3000 French-speaking adults. For women with no history of breast or cervical cancer, multivariate logistic regressions and structural equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 20 publications
(34 reference statements)
1
31
0
Order By: Relevance
“…There have been numerous studies of breast cancer screening among immigrant populations undertaken in other countries 26, 27, 28, 29, 30, 31, 32. Comparing results between studies is challenging as the birth country composition of immigrant populations vary significantly across countries, barriers to screening for immigrants in their adopted country may be different, and the health and cancer screening systems may also differ in significant ways.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies of breast cancer screening among immigrant populations undertaken in other countries 26, 27, 28, 29, 30, 31, 32. Comparing results between studies is challenging as the birth country composition of immigrant populations vary significantly across countries, barriers to screening for immigrants in their adopted country may be different, and the health and cancer screening systems may also differ in significant ways.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, in the French-speaking general population in the same area in 2010, only 8% of women had never been screened for cervical cancer (Rondet et al, 2014). In 2013, a nongovernmental medical organization, Doctors of the World, conducted a survey in France among 203 socially excluded women who visited their free clinics and reported that 70% of them had never been screened (Médecins du Monde, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although national recommendations have been issued since 1990 (which recommend a CCS test every 3 years after two normal tests 1 year apart) (Fédération des Gynécologue et Obstétriciens de Langue Française, 1990), only 10% of women in the recommended age range (25-65 years) have a Pap test at the recommended frequency, 50% have delayed screening or have never been screened and 40% are overscreened, resulting in a national coverage rate that has stagnated at 57% (from 2003 to 2008) [Haute Autorité de Santé (HAS), 2010]. In the French-speaking general population in the Greater Paris area, 8% of concerned women had never been screened for cervical cancer in 2010 (Rondet et al, 2014). Multiple factors associated with an increased risk of no lifetime screening have been reported, such as socioeconomic status and origin (Vallée et al, 2010;Grillo et al, 2012;Rondet et al, 2014), but it has never been studied among homeless women in France.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For equivalent health needs, a more recent study demonstrated that migrants had lower demand for both general practitioner and specialist care (Berchet, 2013). Lastly, migrants from southern Europe and northern Africa were found to be less likely to report preventive health care utilization (for vaccines, blood pressure tests, health check-ups) than their French peers (Wanner, Khlat, and Bouchardy, 1995), and foreign women as a whole to be much less likely to have undergone breast or cervical cancer screening (Grillo, Soler, and Chauvin, 2012;Rondet et al, 2014). Overall, those findings were interpreted as an illustration of unequal access to health care, in relation with language barriers and insufficient knowledge of the health system.…”
Section: Health-related Behavioursmentioning
confidence: 99%